PERAN GAYA MENGAJAR GURU PAI TERHADAP MINAT BELAJAR SISWA KELAS VIII A PADA MATA PELAJARAN PAI DI SMP NEGERI 1 KALIBENING BANJARNEGARA - Hasna Luqyana; Asep Sunarko; Ngatoillah Linnaja (DAS Institute, 2025)
This thesis aims to examine the role of Islamic Religious Education teacher's teaching style on students' interest in learning class VIII A at SMP Negeri 1 Kalibening Banjarnegara. The research objectives include: (1) The concept of teaching style of Islamic Education teachers, (2) Students' learning interest in Islamic Education subjects, (3) Supporting and inhibiting factors in the application of teaching style. This thesis uses a qualitative field research method with a descriptive approach, which describes the phenomenon as it is through direct observation, interviews, and documentation. The research subjects consisted of the principal, PAI teachers, and students of class VIII A at SMP Negeri 1 kalibening Banjarnegara. The results showed that: (1) The teaching style applied by PAI teachers is interactional and participatory, where students are actively involved in the learning process through discussion, question and answer, and contextual approaches that are relevant to everyday life. (2) This teaching style plays an important role in increasing students' interest in learning, which is reflected in the increased attention, motivation, and involvement of students during the learning process. (3) Supporting factors in implementing effective teaching styles include school support, a conducive classroom atmosphere, and teachers' openness in understanding students' needs. The inhibiting factors include limited learning time, less than optimal utilization of technological media, and variations in learning motivation among students. In conclusion, teachers' teaching styles has a significant role in shaping students’ interest in learning the Islamic Religious Education subject.